Natural disaster shocks and macroeconomic growth in Asia: Evidence for typhoons and droughts - Emmanuel Alano; Minsoo Lee (Asian Development Bank (ADB), 2016)
Climate-related natural disaster shocks are expected to rise as the earth is getting warmer, which will adversely affect growth prospects globally. Current robust estimates of the effects of typhoons and droughts point to both short- and long-term declines in national incomes compared to predisaster trends and economic effects likely to persist up to 2 decades. Using the typhoon landfalls and damage in Asia, we analyze the wind-damage relationship and find damages to gross domestic product increase by 2.3% for an increase in maximum wind speed. The extreme projected temperature rise in Representative Concentration Pathway (RCP) 8.5 will result in higher damage by more than 50% in 2100. Vulnerable developing Asian economies could expect dampened growth with significant impacts on agriculture and tourism, a concern that may roll back years of development gains and exacerbate inequality. To cope with increasing disaster risks, both short-term adaptation strategies like relocation, government transfers, and other social safety nets, as well as long-term strategies like disaster insurance or similar ex ante mechanisms are needed.
Keywords: I30; Q54; 330; Asia; climate impact; drought; natural disaster; typhoon